DEFORMATION FIELD, EARTH'S CRUST DEEP STRUCTURE, AND SPATIAL SEISMICITY DISTRIBUTION IN THE TIEN SHAN - Zubovich A.V.; Trapeznikov Yu.A.; Bragin V.D.; Mosienko O.I.; Shchelochkov G.G.; Rybin A.K.; Batalev V.Yu. (My University, 2001)
High density of GPS network in the Tien Shan and long period of observations have allowed us to construct a velocity vector field of movement on the Earth's surface and a strain rate field. A compact uniform area of compressing deformations has been detected. Comparison of the strain rate field with the spatial distribution of weak seismicity for the same period of time showed their considerable correlation. The GPS and seismic data were also compared with data of the magnetotelluric sounding and in particular with geometry of the surface of a crustal conductive layer detected beneath the Tien Shan. The area of maximum compressing deformations coincided with the northern slope of the layer surface, and the strain rate intensity is correlated with the slope angle magnitude of that surface. Nearly all seismic events occur above the surface of the crustal conductive layer. The coincidences suggest that the deformation field and the seismicity distribution are connected by a single tectonic process and depend on the geometry of the crustal layer.